ENHANCING STUDENTS’ PRONUNCIATION THROUGH YOUTUBE CHANNEL: PRONUNCIATION WITH EMMA - Sinta Julia Pratiwi; Hanafi Wibowo (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
The utilize of YouTube for teaching and learning English in this era is needed toimplement. This research aims to investigated YouTube Channel: Pronunciation withEmma able to enhance students’ pronunciation at SMK Bina Mandiri Bekasi. The designof this research is Classroom Action Research (CAR) and uses a quantitative descriptivemethod. Participants in this research were 36 students from XI TKJ F at SMK Bina MandiriBekasi. The result showed that teaching and learning English using YouTube Channel:Pronunciation with Emma as media able to enhance students’ pronunciation.There were significant enhancements both researcher and the student overall performancewithin the classroom. Researcher can make the class more active, and students have gottop notch motivation to learn good pronunciation. Based on data, there is a significantenhance in students’ mean score. In the pre-test, students’ mean score is 71 there were10 students who reached the Minimum Completeness Criteria (KKM) with the percentage27% and 26 students with the percentage 73% failed. Then, in post-test 1 score is 82 therewere 24 students who reached the KKM with the percentage 66% and 12 students with thepercentage 34% failed. In post-test 2 score is 86 there were 34 students who reached theKKM with the percentage 94% and 2 students with the percentage 6% failed. Based onthe result of the mean score cycle 1 and cycle 2, there is enhancement of student’spronunciation that are 82 to 86. It can be concluded that the use of YouTube Channel:Pronunciation with Emma is believed to be successful and able to enhance students’pronunciation.